2018
DOI: 10.1002/ehf2.12264
|View full text |Cite
|
Sign up to set email alerts
|

Worsening renal function definition is insufficient for evaluating acute renal failure in acute heart failure

Abstract: AimsWhether or not the definition of a worsening renal function (WRF) is adequate for the evaluation of acute renal failure in patients with acute heart failure is unclear.Methods and resultsOne thousand and eighty‐three patients with acute heart failure were analysed. A WRF, indicated by a change in serum creatinine ≥0.3 mg/mL during the first 5 days, occurred in 360 patients while no‐WRF, indicated by a change <0.3 mg/dL, in 723 patients. Acute kidney injury (AKI) upon admission was defined based on the rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…8 The components of AKI were recently introduced in the field of AHF. 11 In our previous report, AKI on admission and an increase of ≥0.3 mg/dL in the serum creatinine level during the first 5 days compared with the value on admission were independent predictors of the long-term mortality. 3,9,10 Approximately 30% of AHF patients already have AKI on admission to the intensive care unit (ICU), 3 and such a complication is strongly associated with a poor in-hospital mortality rate and long-term prognosis.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…8 The components of AKI were recently introduced in the field of AHF. 11 In our previous report, AKI on admission and an increase of ≥0.3 mg/dL in the serum creatinine level during the first 5 days compared with the value on admission were independent predictors of the long-term mortality. 3,9,10 Approximately 30% of AHF patients already have AKI on admission to the intensive care unit (ICU), 3 and such a complication is strongly associated with a poor in-hospital mortality rate and long-term prognosis.…”
Section: Introductionmentioning
confidence: 77%
“…3,9,10 Approximately 30% of AHF patients already have AKI on admission to the intensive care unit (ICU), 3 and such a complication is strongly associated with a poor in-hospital mortality rate and long-term prognosis. 11 On the basis of those findings, we concluded that the presence of WRF with AKI on admission might be defined as true WRF. We further suggested the combined concept of WRF and AKI.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Theoretically, XOR activity should be positively correlated with the serum UA levels because the production of UA requires activation of XOR. 25 Second, some of the previous studies excluded patients who had taken XOR inhibitors. 9,10,22 Nevertheless, although XOR activity and serum UA levels were significantly correlated in the present study, the correlation coefficient was not definitive [r = 0.335 (Spearman), data not shown].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously reported that the majority of AHF patients also had acute kidney injury and/or worsening renal function. 25 Second, some of the previous studies excluded patients who had taken XOR inhibitors. In this present study, 18 (62.1%) of the 29 patients in the AHF group who had extremely low XOR activity (≤25 pmol/h/mL) also had a history of XOR inhibitor intake before admission.…”
Section: Factors Associated With High Xanthine Oxidoreductase Activitmentioning
confidence: 99%